P182 Twisted Pouch Syndrome: A Rare, Difficult to Diagnose Mechanical Complication of Ileal Pouch-Anal Anastomosis Amenable to Redo Pouch Salvage Surgery. (21st January 2022) - Holubar MD- MS, S; Qazi, T; Savage, E; Ream, J; Lightner, A; Rieder, F; Gordon, I; Baker, M; Hull, T; Steele, S
Abstract: Background: Ileal pouch-anal anastomosis (IPAA) is a technically demanding procedure. Intraoperatively, great care must be taken to assure a straight superior mesenteric axis. Rarely, twisted pouches are inadvertently constructed, resulting in deviations of expected pouch function. Herein we describe our quaternary pouch referral center experience with twisted pouch syndrome (TPS). Methods: We performed a retrospective review of our prospectively maintained pouch registry from 1995 – 2020. Patients were identified using free-text search of redo IPAA operative reports for variations of the term "twist". We defined twisted pouch syndrome as intraoperative findings of twisting of the pouch around its mesenteric axis which could not be reduced without disconnection from the anus. Data represent frequency (proportion) or median (range). Results: Over 25-years, we identified 31 patients with confirmed TPS who underwent a redo pouch procedure by 11 surgeons: 67% were female, median BMI 21.2 (16.9 – 29.5) kg/m 2 . The duration from the index IPAA to redo procedure was 5 (0.5 – 21) years; all (100%) were referral cases constructed elsewhere. Original diagnoses included: ulcerative colitis 28 (90%), FAP 2 (6.5%). All patients presented with symptoms of pouch dysfunction including erratic bowel habits 28 (93%) with urgency and frequency, abdominal/pelvic/rectal pain 26 (87%), and obstructive symptoms 28 (93%) i.e. obstructed defecation and incomplete evacuation. Most had (75%) been treated for chronic pouchitis with medical therapy, and 48% had undergone previous surgery. Prior to redo IPAA procedure patients underwent a thorough workup: 100% pouchoscopy, 94% pouchogram, 87% underwent EUA, 87% MRI/CT, 71% manometry, and 39% defecography. TPS was diagnosed in 16% by pouchoscopy, in 13% by imaging, and in 71% was diagnosed intra-operatively at re-diversion (20%) or revision/redo IPAA (51%). In terms of surgical intervention, 81% were initially re-diverted. A total of 18 (60%) underwent pouch revision, and 12 (40%) required neo-IPAA. Short-term outcomes: LOS 8 (3 – 32) days, any complication 48%, readmission 11%, reoperation 3.4%, zero mortalities. After a median follow-up 52.5 (1 – 206) months, there were 4 failures: 2 never had loop ileostomy closure, 1 pouch excision, 1 Kock pouch, yielding an overall pouch survival rate of 87%. Conclusion: Twisted pouch syndrome presents with pouch dysfunction manifest by the triad of erratic bowel habits, unexplained pain, and obstructive (defecation) symptoms. This syndrome may also mimic chronic pouchitis. Despite a thorough workup suggesting a mechanical problem, many patient are not diagnosed until time of redo pouch surgery. Redo surgery for twisted pouch syndrome results in long-term pouch survival for the majority.